Distribution and Selected Beta-Lactam Susceptibility of Escherichia coli and Staphylococcus aureus in Suspected Sepsis Patients at RSUD Ir. Soekarno - Yusianti Silviani; Mustofa Tri Wijayanto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Sepsis is a life-threatening organ dysfunction caused by a dysregulated host response to infection, and antimicrobial resistance may compromise empirical therapy. This retrospective descriptive study described the distribution of Escherichia coli and Staphylococcus aureus and selected beta-lactam susceptibility patterns among patients with suspected sepsis at RSUD Ir. Soekarno Sukoharjo during 2024–2025. Secondary data from blood, urine, sputum, and pus cultures, including antimicrobial susceptibility testing using the VITEK 2 Compact system, were analyzed descriptively as counts and proportions. Escherichia coli accounted for five isolates in 2024 and four in 2025, whereas Staphylococcus aureus was represented by one isolate in 2024 and was not identified in 2025. Resistance to ceftazidime was observed in 3/5 (60.0%) Escherichia coli isolates in 2024 and 3/4 (75.0%) in 2025, while ceftriaxone resistance occurred in 4/5 (80.0%) and 3/4 (75.0%), respectively. The single Staphylococcus aureus isolate was resistant to oxacillin and phenotypically consistent with MRSA. These findings indicate frequent resistance to third-generation cephalosporins among a small number of Escherichia coli isolates. Interpretation should be cautious because of the limited number of isolates and the absence of confirmatory ESBL or MRSA testing data.